The Effect of Religiusity to Premarital Ethics Violation in SMA/SMK Students in Siak District, Riau Province - Thahariyah Thahariyah; Munawar Rahmat; Udin Supriadi (STAIN Bengkalis, 2021)
Premarital etiquette violations are quite disturbing. Various research results show a high percentage of premarital sex. But various studies also show the influence of religiosity on risky sex. The research aimed to find the relationship between religiosity and violations of premarital ethics among SMA/SMK students in Siak Regency, Riau Province. Description-correlational research methods. The research sample was 223 students. The religiosity inventory of 81 items and 26 inventory items of pre-marital ethics violations were submitted to them. Data analysis used descriptive statistics (%-tase) and regression tests. The result, first, the respondent's religiosity is quite good. Second, the respondents' premarital ethics violations were relatively low. Third, there is an inverse correlation between religiosity and violations of premarital ethics. The higher the respondent's religiosity, the lower the violation of premarital ethics. Likewise, vice versa. The pedagogical implication of this research is that religious education is very important in maintaining the sanctity of SMA/SMK students.